2019
DOI: 10.5194/isprs-archives-xlii-4-w16-621-2019
|View full text |Cite
|
Sign up to set email alerts
|

Uav-Based Hyperspectral Data Analysis for Urban Area Mapping

Abstract: Abstract. A recent development in low-cost technology such as Unmanned Aerial Vehicle (UAV) offers an easy method for collecting geospatial data. UAV plays an important role in land resource surveying, urban planning, environmental protection, pollution monitoring, disaster monitoring and other applications. It is a highly adaptable technology that is continuously changing in innovative ways to provide greater utility. Thus, this study aimed to evaluate the capability of UAV-based hyperspectral data for urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, there are existing gaps in satellite imagery that limit its effectiveness in capturing the fine-scale details and monitoring dynamic urban environments. These gaps include limitations in the spatial resolution, temporal coverage, and cloud cover interference [40,41]. These limitations hinder accurately assessing and monitoring climate-related phenomena in urban areas.…”
Section: Uavs and Data Capabilitiesmentioning
confidence: 99%
“…However, there are existing gaps in satellite imagery that limit its effectiveness in capturing the fine-scale details and monitoring dynamic urban environments. These gaps include limitations in the spatial resolution, temporal coverage, and cloud cover interference [40,41]. These limitations hinder accurately assessing and monitoring climate-related phenomena in urban areas.…”
Section: Uavs and Data Capabilitiesmentioning
confidence: 99%
“…The authors of [76] reported an OA of 87.75% for RF, 83.31% for CNN, and 80.29% for SVM due to mapping using the Random Forest (RF), CNN, and SVM models. In [77], the classification of urban areas was evaluated using ANN, SVM, ML, and SAM, and the overall accuracies obtained were 92.33%, 85.86%, 83.41%, and 46.55%, with Kappa coefficients of 0.91, 0.83, 0.80, and 0.38, respectively. The ANN method was reported to be effective.…”
Section: Assessment Of Classification Techniquesmentioning
confidence: 99%